Export Behaviour in Chilean Exporters in Service Sector [la Conducta Exportadora de Las Empresas Chilenas Exportadoras del Sector de Servicios] - Torres-Zapata, I (Emerald Group Holdings Ltd., 2018)
Purpose: The purpose of this paper is to describe and explain the export behaviour (EB) developed by the Chilean service sector exporter firms using longitudinal data, to contribute to the scarce literature in this field in emerging markets. Design/methodology/approach: Chilean service sector exporter firms are studied through a longitudinal analysis (2006 to 2015) comparing EB (continual/discontinual exporters) with respect to market diversification (MD). Considering a quantitative hypothesis test, based on a t-test, comparing these two groups of firms, using STATA software. Findings: According to this research, scarce MD promotes a discontinual export development process in Chilean service sector exporter firms. Practical implications: It is important to define public policies focussed on maintaining exportation over time and also to support these firms in diversifying their markets. Originality/value: This paper shows a means of analysis, using longitudinal data, to compare large groups of firms, describing the causes of the discontinual export development process. At the same time, it enhances the literature on service sector exporters. © 2018, Emerald Publishing Limited.